Kekristenan dan Budaya Batak: Sinergi antara Iman dan Tradisi - Landong Sihombing; Putri Sihite; Raja Pangihutan Sitompul (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This article discusses the synergy between Christianity and Batak culture, which is characterized by a reciprocal relationship that changes each other. The process of inculturation of the Christian faith in Batak society shows that religion is not only passively adopted, but is also adapted to meet the spiritual needs of the community. This research reveals how the Batak people who adhere to Christianity try to maintain their cultural identity while integrating the values ​​of the Christian faith. This can be seen in various traditional ceremonies which are now adapted to the Christian context, such as the use of ulos motifs in church liturgy and the incorporation of traditional music in worship. The synergy between Christianity and Batak culture has significant social implications, creating space for dialogue between the older and younger generations regarding the importance of maintaining traditions while opening up to new teachings. Thus, this article highlights the complexity of the interaction between Christianity and Batak culture and the importance of understanding the inculturation process as part of the social and spiritual dynamics of society.